Effect on Nitrogen Balance, Thermogenesis, Body Composition, Satiety, and Circulating Branched Chain Amino Acid Levels up to One Year after Surgery: Protocol of a Randomized Controlled Trial on Dietary Protein During Surgical Weight Loss - Moizé, Violeta (JMIR Res Protoc, 2016)
BACKGROUND: Bariatric surgery (BS), the most effective treatment for severe obesity, typically results in 40-50 kg weight loss in the year following the surgery. Beyond its action on protein metabolism, dietary protein intake (PI) affects satiety, thermogenesis, energy efficiency, and body composition (BC). However, the required amount of PI after surgical weight loss is not known. The current daily PI recommendation for diet-induced weight loss is 0.8 g/kg ideal body weight (IBW) per day, but whether this amount is sufficient to preserve fat-free mass during active surgical weight loss is unknown. OBJECTIVE: To evaluate the effect of a 3-month dietary protein supplementation (PS) on nitrogen balance (NB), BC, energy expenditure, and satiety in women undergoing either gastric bypass or vertical sleeve gastrectomy. METHODS: In this randomized prospective study, participants will be randomized to a high protein supplementation group (1.2 g/kg IBW per day) or standard protein supplementation group (0.8 g/kg IBW per day) based on current guidelines. Outcome measures including NB, BC, circulating branched chain amino acids, and satiety, which will be assessed presurgery, and at 3-months and 12-months postsurgery. RESULTS: To date, no studies have examined the effect of dietary PS after BS. Current guidelines for PI after surgery are based on weak evidence. CONCLUSIONS: The results of this study will contribute to the development of evidence-based data regarding the safe and optimal dietary PI and supplementation after BS. TRIAL REGISTRATION: Clinicaltrials.gov NCT02269410; http://clinicaltrials.gov/ct2/show/NCT02269410 (Archived by WebCite at http://www.webcitation.org/6m2f2QLeg).